Connectance and nestedness as stabilizing factors in response to pulse disturbances in adaptive antagonistic networks. (7th February 2020) - Baumgartner, Matheus T.
Highlights: Frequency and intensity of disturbances may affect communities differently depending on the network structure. Network properties were related to community robustness against pulse disturbances that caused reductions in the abundance of resources. Simulations considered 45 empirical networks under five disturbance scenarios of frequency and intensity of disturbances. In each disturbance event, the abundance of resources were reduced and the subsequent effects on consumers were evaluated. Connectance and nestedness had a stabilizing role in communities. The effects of resources' shortages were more discrete in highly connected and nested networks. Abstract: Understanding how network architectures are related to community robustness is essential to investigating the effects of disturbances on biological systems. Regarding the perturbations that are observed in disturbance regimes, frequency and intensity are two main descriptors, specifically for those events with short duration. Here, I used the architecture of 45 real-world weighted bipartite networks to assess whether network size, connectance, and nestedness are related to the effects of pulse disturbances in antagonistic communities. Networks were simulated under five scenarios with different combinations of frequency and intensity of perturbations. The dynamics of resource-consumer interactions followed the adaptive interaction switching behavior, which is the key topological process underlying most of the architectures of antagonistic webs. As opposed to most studies considering the effects of disturbances as species extinctions explicitly, the effects of disturbances here were modeled as changes in the abundance of consumers following immediate reductions in the abundance of resources. Simulations revealed that community robustness to pulse disturbances increased with both connectance and nestedness overall, with no effect of network size. Community networks with highly connected and nested topologies were more robust to disturbances, particularly under high frequency and intensity perturbations. By considering disturbances that are not directly related to species' extinctions, this study provides valuable insights that connectance and nestedness have an important stabilizing role in ecological networks.